2016
DOI: 10.1080/03009742.2016.1206617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive impairment, depression, disease activity, and disease damage on quality of life in women with systemic lupus erythematosus

Abstract: Our results highlight the relevance of executive dysfunction to poor physical and mental health components of HRQoL in SLE together with depression, while disease activity and disease damage are associated with lower HRQoL physical components. The need for cognitive function evaluation and rehabilitation in SLE is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 35 publications
2
38
0
3
Order By: Relevance
“…Previous reports have confirmed that, in addition to age and disease duration, other factors can affect HRQoL in people with SLE, such as socioeconomic status, disease activity and psychiatric disorders . Although the interaction between these factors is probably complex, identifying the treatable determinants may help to improve SLE patients’ HRQoL and perceived well‐being, especially when the decline in HRQoL does not seem to be the result of SLE disease activity.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have confirmed that, in addition to age and disease duration, other factors can affect HRQoL in people with SLE, such as socioeconomic status, disease activity and psychiatric disorders . Although the interaction between these factors is probably complex, identifying the treatable determinants may help to improve SLE patients’ HRQoL and perceived well‐being, especially when the decline in HRQoL does not seem to be the result of SLE disease activity.…”
Section: Discussionmentioning
confidence: 96%
“…The association of circulating anti-P with lupus psychosis [ 68 ] has been well documented [ 69 , 70 ]. Clinical [ 23 ] and experimental evidence [ 19 , 20 ] also involve anti-P in CD, which is the most frequent NPSLE manifestation [ 2 ], independent of depression [ 71 ], and may contribute to reduce health-related quality of life in SLE patients [ 3 ]. Both psychotic and cognitive disorders involve alterations in glutamatergic receptors [ 6 , 24 , 72 ] and can be elicited by a variety of different antibodies [ 21 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal surface P antigen (NSPA) is a protein of unknown function originally discovered as a cross-reacting target of anti-ribosomal P protein autoantibodies (anti-P) that associates with neuropsychiatric manifestations, particularly psychosis and cognitive dysfunction (CD), in patients with systemic lupus erythematosus (SLE) [ 1 ]. CD is common among neuropsychiatric SLE (NPSLE) manifestations, affecting up to 80% of SLE patients [ 2 ]; it associates with a decreased quality of life [ 3 ] and has no targeted therapy at present [ 2 ]. Elucidating NSPA function in neurons can reveal mechanistic clues to better understand antibody-driven CD in NPSLE and could uncover new neuronal alterations leading to neuropsychiatric disease, from which more specific treatments might emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction (CD) is one of the most common of the 19 neuropsychiatric lupus (NPSLE) syndromes and manifests insidiously over time, as opposed to the more dramatic presentations of acute confusional state, stroke, and psychosis (1,2). CD in systemic lupus erythematosus (SLE) affects multiple cognitive domains, including attention, executive function, verbal and nonverbal learning, working memory, and psychomotor function; it is associated with significantly increased morbidity and decreased quality of life (3)(4)(5)(6). The diagnosis of CD and correct attribution to SLE-associated mechanisms rather than other potentially confounding factors, such as infection, metabolic disturbances, medication effects, mood disturbances, and toxins, have been compromised by the poor sensitivity and specificity of available diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%